Meta-pipeline: A new execution mechanism for distributed pipeline processing - Yamagiwa, S. (2007)
The Caravela platform has been proposed by the authors of this paper to perform distributed stream-based computing on general purpose computation. This platform uses a secured execution unit called flow-model that prevents remote users to touch local information in a computer. The flow-model is assigned to local or remote processing units that execute its program. This paper is focused on a new execution mechanism that defines a pipeline composed by flow-models, called meta-pipeline, and is designed as a set of additional functions of the Caravela platform. The pipeline is executed automatically by the meta-pipeline runtime environment. This paper describes the execution mechanism and also presents an application example.